Morphological variation among fifteen superior robusta coffee clones in Lampung Province, Indonesia - SRI RAMADIANA; DWI HAPSORO; YUSNITA YUSNITA (Biodiversitas Journal of Biological Diversity, 2018)
Ramadiana S, Hapsoro D, Yusnita Y. 2018. Morphological variation among fifteen superior robusta coffee clones inLampung Province, Indonesia. Biodiversitas 19: 1475-1481. This study aimed to characterize morphological variation among fifteensuperior robusta coffee clones in Lampung Province. The fifteen clones consisted of four clones released by the Indonesian Coffee andCocoa Research Institute (ICCRI), i.e. ‘BP 409’,‘BP936’, ‘BP939’, ‘SA 237’, together with eleven superior coffee clones selected byfarmers from Tanggamus District (‘Tugino’, ‘Wanto’, ‘Biyadi’, ‘Komari’, ‘Wardi’, ‘Wariso’) and from West Lampung District (‘TuguKuning’, ‘Tugu Hijau', ‘Tugu Biru', ‘Tugu Sari', ‘Lengkong'). Fifteen qualitative and seven quantitative morphological characters wereevaluated in a randomized complete block design with three replicates for each clone,each replication consisted of two plants. Fromeach plant, four samples were taken from four sides of the plant (north, south, west, and east). It was found that while somemorphological characters exhibited negligible variation among clones, there were significant differences between clones for othercharacters. The characters that did not differ significantly between clones were: shapes of leaf base and leaf tip; petiole color; leafvenation pattern; fruit disk shape; ripe-fruit color; and stipule shape. The characters that varied between clones were shape of leaf lamina(elliptical vs. lanceolate); fruit shape (round vs. oval); and shape of leaf margins. Morphological variation was also observed in somequantitative characters: canopy diameter; tree height; stem diameter; leaf length; leaf width; petiole length; stipule length; and number ofprimary branches.